Seenreport Portal - Kagendo, Edna (Meru: Kagendo Edna, 2013)
Seenreport portal is a system that is designed to enable people report on news as they see them happen.The portal provides a suitable and easy display for which large population around the world can learn or will have the knowledge about the world. The idea is anyone can send a news item using their web which is managed by administrator to whom the editors' panel kept in charge for this to make it visible for the masses. This portal is developed using HTML,PHP & CSS technologies and SQL Server.Seenreport portal will enable people to air their views wherever they are. The system will help promote citizen journalism where different people from all races can share events happening around them. It will also allow people to get timely news as they happen this is because the news will be posted immediately they take place.The system will also be used as a tool to reduce criminal activities such as drug trafficking and other different types of crime.Seenreport portal can also be purchased by different media houses such as the radio stations, the television stations and customized to suit their requirements. This software will therefore enable them to collect news from their fans.
A research project report submitted in partial fulfillment of the requirements for the award of degree in computer technology of the Meru University of Science and Technology.